Обґрунтування обладнання для збирання льону олійного зернозбиральним комбайном - Дідух, В. Ф.; Буснюк, В. В.; Бодак, М. В.; Didukh, V.; Busyijk, V.; Bodak, M. (ЦНТУ, 2022)
В статті проводиться аналіз технологій збирання льону олійного з використанням зернозбирального комбайна. Тривалі дослідження у Луцькому НТУ вказують на можливість застосування брання стеблостою льону олійного. Запропонована конструкція широкозахватного брального апарату для даного способу з врахуванням сучасної методології створення сільськогосподарської техніки. Визначено необхідні робочі органи, які забезпечують формування потоку групи стебел і передачу їх на жатку зернозбирального комбайна. Встановлена умова нерозривності потоку групи стебел для забезпечення рівномірної подачі у молотильний апарат для якісного відділення насіння. Presentation of the results of experimental field research, laboratory to determine the conditions for harvesting oilseed flax stalks in the phase of full maturity. Outlining the conditions for the technological operation of harvesting oilseed flax by extracting stems from the soil. Presentation of the methodology for determining the necessary working elements of the equipment for extracting stems from the soil and forming the continuity of the flow of a group of stems on the harvesting part of the combine harvester. The problem that arises in the process of harvesting flax oil in the phase of full maturity is due to the presence of fiber in the stems, which complicates the work of the segmental-finger cutter. Therefore, the collection of such stems is carried out by the method of taking (extraction from the soil). This phenomenon requires the development of equipment for the universalization of the combine harvester, which increases its ability to be used in the harvesting of crops, taking into account the growing conditions and the state of the stalk. The experiments were conducted in the field on the Lyrina variety to establish the average value of the collection effort. The crops were not characterized by uniform ripening, which allowed to choose areas that characterized the maturity phases of oilseed flax. Start of research: mid-July, end - until 01.09. Accordingly, the study of the continuity of flow was conducted in the laboratory by simulating the selection of stems from one to five adjacent rows. It was found that a cylindrical support rough surface is required to ensure the continuity of the flow in the equipment. Based on the proposed structural and logical scheme, the main working units of the equipment to ensure high-quality harvesting of oilseed flax of any phase of ripeness without changing the design of the harvesting part of the combine harvester. These include: the mechanism of separation of portions of the stem from the total array and the picking device, which consists of pairs of rollers with horizontal axes of rotation and a distance between them of 76.2 mm. Combining the results of field and laboratory studies with the analysis of forces when moving the stem mass in the form of a flow of a group of stems on the supporting surface allowed to offer a constructive - layout scheme of equipment for harvesting oilseed flax. This equipment is intended to be installed on the harvesting part of the combine without changing its design. The analysis of forces performed for the flow of stems moving inseparably on a cylindrical support surface is important for the study of the selection of the stem mass of crops from rolls.
Substantiation of Equipment for Harvesting Oil Flax with a Combine Harvester
Keywords: льон олійний; брання; обладнання; комбайн; стеблостій; група стебел; потік; насіння; сили; вальці; опорна поверхня; flax; equipment; combine; stalk; flow; seeds; surface